2021
DOI: 10.1021/acs.jcim.1c00150
|View full text |Cite
|
Sign up to set email alerts
|

Molecular View on the Dissociation Pathways and Transactivation Regulation Mechanism of Nonsteroidal GR Ligands

Abstract: As a major drug target for anti-inflammatory therapy, the glucocorticoid receptor (GR) regulates a wide range of physiological processes through transactivation (TA) or transrepression. GR TA is involved in many adverse effects of GR-targeting drugs, and therefore, the discovery of novel GR ligands with lower TA activity and longer residence time is quite urgent. Undoubtedly, understanding the ligand dissociation mechanisms and the structural basis of the TA regulation is crucial for the development of novel G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 53 publications
(105 reference statements)
0
4
0
Order By: Relevance
“…Previous studies have indicated that the ligand entry pathway into the nuclear receptor involves a channel between helix‐3, helix‐7, and helix‐11. [ 24 ] Considering the possibility of alternative pathways for ligand dissociation from the nuclear receptor, [ 25 ] we first used the random accelerated MD (RAMD) [ 26 ] method to explore the dissociation pathways of the four ligands from the AR‐LBP. Each system was run with 40 parallel replicas, and the results are shown in Table S1 (Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have indicated that the ligand entry pathway into the nuclear receptor involves a channel between helix‐3, helix‐7, and helix‐11. [ 24 ] Considering the possibility of alternative pathways for ligand dissociation from the nuclear receptor, [ 25 ] we first used the random accelerated MD (RAMD) [ 26 ] method to explore the dissociation pathways of the four ligands from the AR‐LBP. Each system was run with 40 parallel replicas, and the results are shown in Table S1 (Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…A higher value of residence time increases the duration of drug action and leads to greater physiological inhibition. 77 Here, residence time (τ) was calculated from RAMD (it is not the physical residence time, but rather adaptive for the comparative study of residence time for inhibitors 78 ) for the inhibitors in each of the five kinase-inhibitor complexes (Figure S16). Comp1 showed a higher τ value (0.38 ns) in the WT system, whereas Comp2 showed a higher value (τ = 0.48 ns) for the mutated system (Table 3).…”
Section: Results From Principal Component Analysis (Pca)mentioning
confidence: 99%
“…Nevertheless, because the biomacromolecule-relevant events often occur several orders of magnitude beyond a conventional MD (cMD) affordable simulation time, enhanced sampling techniques emerge, with algorithms such as random acceleration molecular dynamics (RAMD), umbrella sampling (US), metadynamics (MetaD), steered molecular dynamics (SMD), etc., widely applied in the tasks of identifying kinetic characteristics of drug-target interactions ( e.g. , the NR targets). For instance, by using SMD and LES-MD simulations successively, Martinez et al revealed that the conformational rearrangement of the relevant residues in TRα/β leads to the dissociation of the ligand and furthermore interpreted the drug selectivity of the two NR targets. , Moreover, in a recent review, the authors summarized that the NRs may share several potential dissociation pathways because a similar fold structure is held by the NRs, but there are individual differences in certain NR members . However, most of the studies usually investigate a few systems ( e.g.…”
Section: Introductionmentioning
confidence: 99%